SPEECH STYLE USED IN CHILD DEVELOPMENT - Hastuti, Sri; Mahmud, Murni; Weda, Sukardi (Journal of English Literature and Linguistic Studies, 2023)
This study is about Speech Style Used in Child Development. The aim of this research is to find out the different speech styles used in child development. The researcher has compared what speech styles that are used. Such as, formal style, frozen style, intimate style, casual style and consultative style. The theory chosen by the researcher about speech style is the theory of Martin Joos which classifies speech styles into five. There are two problems formulated in this study: (1) What are the differences between active children and passive children? (2) What are the functions of each type of speech style used by active children and passive children? The researcher has compared. The method used in this research Qualitative method and Sociolinguistics approach. This research investigated 11 students in one grade in Madrasah Ibtidaiyah (MI) Karama. In this analysis, the researcher found 4 out of 5 types of speech style, the researcher found consultative style, casual style, intimate style and formal style. Then, for the functions, the researcher also found 3 out of 5 types of speech. The researcher found expressive, directive and representative.